The Curricular Policy of the Ministry of Public Education of Costa Rica: An Approach from the Voices of Three Regional Education Boards - Vargas Jiménez, Ileana (2025)
This paper is based on the Perfiles, dinámicas y desafíos de la educación costarricense project, which is affiliated with the Center for Research and Teaching in Education (CIDE in Spanish) at the Universidad Nacional. The research was conducted from 2022 to 2024. The authors analyzed the perceptions of three regional directors of the Costa Rican education system from the regions of Alajuela, San José oeste, and Coto, their views on the 2015 curriculum policy, and their role in its management and implementation. The question addressed was What are the greatest challenges posed by the requirements of the current curriculum policy for regional directors? The methodology used a qualitative approach and phenomenological method; semi-structured interviews were conducted with the regional directors of the aforementioned regions. The findings indicate that the current curriculum policy remains in effect, with connectivity problems and lags; developing adequate pedagogical mediation is a challenge. Finally, the conclusions reflect that students are at the center of curriculum policy, that the COVID-19 pandemic posed a complex issue to address, that connectivity within institutions represents a pressing situation, and that there are gaps in literacy learning, and this must be addressed by educational institutions, together with the management of participating regional director boards.